Finding Jerusalem : Archaeology between Science and Ideology - Galor, Katharina (University of California Press, 2017)
Archaeological discoveries in Jerusalem capture worldwide attention in various media outlets. The continuing quest to discover the city$1 (Bs physical remains is not simply an attempt to define Israel$1 (Bs past or determine its historical legacy. In the context of the ongoing Israeli-Palestinian conflict, it is also an attempt to legitimate$1 (Bor undercut$1 (Bnational claims to sovereignty. Bridging the ever-widening gap between popular coverage and specialized literature, Finding Jerusalem provides a comprehensive tour of the politics of archaeology in the city. Through a wide-ranging discussion of the material evidence, Katharina Galor illuminates the complex legal contexts and ethical precepts that underlie archaeological activity and the discourse of (3z(Bcultural heritage(3y (Bin Jerusalem. This book addresses the pressing need to disentangle historical documentation from the religious aspirations, social ambitions, and political commitments that shape its interpretation. (3z(BA brilliant book on the contested historical roles of archaeology in modern Jerusalem, a city torn by religious, ideological, and political conflicts. This is a must-read for both scholars and laymen interested in the fascinating, tormented history of the Holy City.(3y (B-YARON EZRAHI, Professor Emeritus of Political Science, Hebrew University of Jerusalem (3z(BIn a work made possible by her remarkable ability to move between Israeli and Palestinian perspectives, Galor uncovers the political dimensions of archaeology as practiced in Jerusalem, bringing to bear her expertise as an archaeologist and an intimate knowledge of the city and its history.(3y (B-STEVEN WEITZMAN, Abraham M. Ellis Professor of Hebrew and Semitic Languages and Literatures and Ella Darivoff Director of the Katz Center for Advanced Judaic Studies, University of Pennsylvania KATHARINA GALOR teaches Judaic Studies and Urban Studies at Brown University. She is the coauthor of The Archaeology of Jerusalem: From the Origins to the Ottomans.s
Knowledge Unlatched
English
Keywords: Religion & beliefs; Humanities; Religion; General; History; General